Early Intervention to Improve Sucking in Preterm Newborns: A Systematic Review of Quantitative Studies. (April 2019) - Grassi*, Angela; Sgherri*, Giada; Chorna, Olena; Marchi, Viviana; Gagliardi, Luigi; Cecchi, Francesca; Laschi, Cecilia; Guzzetta, Andrea
Abstract : Background: Premature birth is associated with feeding difficulties due to inadequate coordination of sucking, swallowing, and breathing. Nonnutritive sucking (NNS) and oral stimulation interventions may be effective for oral feeding promotion, but the mechanisms of the intervention effects need further clarifications. Purpose: We reviewed preterm infant intervention studies with quantitative outcomes of sucking performance to summarize the evidence of the effect of interventions on specific components of sucking. Methods: PubMed, CINAHL, MEDLINE, EMBASE, and PSYCOLIST databases were searched for English language publications through August 2017. Studies were selected if they involved preterm infants, tested experimental interventions to improve sucking or oral feeding skills, and included outcome as an objective measure of sucking performance. Specific Medical Subject Headings (MeSH) terms were utilized. Results: Nineteen studies were included in this review: 15 randomized, 1 quasi-randomized, and 3 crossover randomized controlled trials. Intervention types were grouped into 6 categories (i) NNS, (ii) NNS with auditory reinforcement, (iii) sensorimotor stimulation, (iv) oral support, (v) combined training, and (vi) nutritive sucking. Efficiency parameters were positively influenced by most types of interventions, though appear to be less affected by trainings based on NNS alone. Implications for Practice: These findings may be useful in the clinical care of infants requiring support to achieve efficient sucking skills through NNS and oral stimulation interventions. Implications for Research: Further studies including quantitative measures of sucking performance outcome measures are needed in order to best understand the needs and provide more tailored interventions to preterm infants.